2006
DOI: 10.1093/hmg/ddi479
|View full text |Cite
|
Sign up to set email alerts
|

Loss of emerin at the nuclear envelope disrupts the Rb1/E2F and MyoD pathways during muscle regeneration

Abstract: Emery-Dreifuss muscular dystrophy (EDMD1) is caused by mutations in either the X-linked gene emerin (EMD) or the autosomal lamin A/C (LMNA) gene. Here, we describe the derivation of mice lacking emerin in an attempt to derive a mouse model for EDMD1. Although mice lacking emerin show no overt pathology, muscle regeneration in these mice revealed defects. A bioinformatic array analysis of regenerating Emd null muscle revealed abnormalities in cell-cycle parameters and delayed myogenic differentiation, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
238
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(250 citation statements)
references
References 63 publications
12
238
0
Order By: Relevance
“…It is known that lamin A/C and emerin are involved in muscle transcriptional pathways [33][34][35][36][37]. One study proposed that LAP1 might bind indirectly to mitotic chromosomes via a linker protein [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that lamin A/C and emerin are involved in muscle transcriptional pathways [33][34][35][36][37]. One study proposed that LAP1 might bind indirectly to mitotic chromosomes via a linker protein [9].…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation will be required to understand the onset of nuclear membrane instability upon loss of TDP-43. Interestingly, recent work showed that nuclear membrane dysfunction, particularly loss of emerin, is tied to misregulation of pRb pathway components (40,41) suggesting that nuclear membrane abnormalities caused by TDP-43 loss are mediated by pRb. These conclusions are supported by the lack of apoptosis and nuclear membrane disruption after TDP-43 silencing in Saos-2 cells that lack a functional pRb pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo regeneration of cardiotoxin treated Lmna −/− muscles appears to proceed normally and primary Lmna −/− myoblast cultures do not show any impairment in their differentiation to myotubes [21]. However immortalized Lmna −/− myoblasts are impaired in their differentiation to myotubes, [22], suggesting that the process of immortalization affects the myoblasts dependency on having a functional lamina for differentiation to proceed.…”
Section: The A-type Laminopathiesmentioning
confidence: 96%
“…Temporal activation of MyoD transcriptional targets was significantly delayed, whereas targets of the Rb1/E2F transcriptional repressor complex remained inappropriately active resulting in a delay in myoblast/myotube transition during regeneration. Cultured primary myoblasts from Emd null mice also showed a delay in fusing to form myotubes, which correlated with prolonged Rb1 hyperphosphorylation [21]. Despite these anomalies, mice (at least 1 year old) lacking emerin do not develop muscular dystrophy or cardiac conduction defects, suggesting that, in mice, loss of emerin may have few pathological consequences [21,23].…”
Section: The A-type Laminopathiesmentioning
confidence: 99%